€€×&ruhrbdhhbfhqklobd221jejdnncxchmekpalednnxhjdnnchjfjrj
Step-by-step explanation:
hzhnrbchchjnncnchgkqlpqjehsnkkeplfgbhfssgbchkekemdmjcjj2oohuetywioqpeuywiopddhuxnncbnsmmajsnbdbvxhdj jndnnfhj b3jjdjdjd ndjnnfhcnn jndncjkakksj hdhjchjcj ndnnbcjc bdhnxjjdjjdk njjdjdjckkf hdjjdhxjjx hdhjcjjcjnrfj hsjnk
Answer:
y intercept = (0,-2)
x intercept = (-2,0)
Step-by-step explanation:
For y intercept, plug 0 for x
y = (0) - 2
y = -2
y intercept = -2
For x intercept, plug 0 for y
(0) = -x - 2
Move -2 to other side
-x = 2
Since x is negitave, make 2 negitave
x = -2
x intercept = -2
y=2x+4
that is an equation in slope intercept form where the slope is 2 so you would go up two right 1 and the y intercept would be 4 so (0,4)